2020
DOI: 10.3390/microorganisms8121920
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Extraction and Characterization of Nitrogen-Containing Azaphilone Red Pigments and Ergosterol Derivatives from the Marine-Derived Fungal Talaromyces sp. 30570 Strain with Industrial Relevance

Abstract: Many species of Talaromyces of marine origin could be considered as non-toxigenic fungal cell factory. Some strains could produce water-soluble active biopigments in submerged cultures. These fungal pigments are of interest due to their applications in the design of new pharmaceutical products. In this study, the azaphilone red pigments and ergosterol derivatives produced by a wild type of Talaromyces sp. 30570 (CBS 206.89 B) marine-derived fungal strain with industrial relevance were described. The strain was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…30570 marine-derived fungal strain, 6 among which were occurred only when complex organic nitrogen sources were present in the culture medium. These structures contained an amino acid residues [ 35 ]. Sun et al also demonstrated the influences of exogenous glucose and pyruvate on the polyketide product flaviolin in an engineered E. coli BL21(DE3) [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…30570 marine-derived fungal strain, 6 among which were occurred only when complex organic nitrogen sources were present in the culture medium. These structures contained an amino acid residues [ 35 ]. Sun et al also demonstrated the influences of exogenous glucose and pyruvate on the polyketide product flaviolin in an engineered E. coli BL21(DE3) [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pigments produced in Pigment Complex A were first analyzed by UV/Vis diode array chromatography. Using the same chromatographic conditions, we proceeded to the determination of these compounds using HR-MS. For the identification of the compounds, we searched the current literature for the known metabolites of Penicillium purpurogenum [ 18 , 19 , 20 ], collected all the reported compounds and created an in-house library containing their chemical structures. We used this library in conjunction with Bruker’s MetaboBASE Plant Library to annotate the compounds being reported in Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“…The third pigment (sassafrinamine A) (3) is purple and displays a nitrogen into the isochromene system substituted with ethyl-1-ol group (Figure 2). The fungus Aspergillus cavenicola afforded the nitrogenated azaphilones trans-cavernamine (4), ciscavernamine (5), amino acid derivatives of cis-cavernamines (6-10), hydroxy-cavernamine (11), amino acid derivatives of hydroxy-cavernamines (12)(13)(14)(15)(16), and two oxygenated derivatives cis and trans-cavernines (17)(18) [34]. The marine-derived fungus Aspergillus falconensis yielded five mitorubrins derivative azaphilones with different benzoyl moieties: two new chlorinated azaphilones, falconensins O and P (19 and 20) when the fungus was cultivated in a solid rice medium containing 3.5% NaCl and three additional new azaphilone derivatives (21)(22)(23) when NaCl was replaced by 3.5% NaBr [35].…”
Section: Azaphilones From Aspergillus Genusmentioning
confidence: 99%
“…Eco-friendly solvents were chosen for the extraction (90 °C and 10 MPa) as water, methanol and/or ethanol. At the end, twelve nitrogen-containing azaphilone red pigments were identified while known mycotoxins were not produced [ 13 ]. Two-phase aqueous extraction [ 107 ] was successfully tested for the extraction of pigments from T. albobiverticillius .…”
Section: Processing and Innovations In Azaphilones Productionmentioning
confidence: 99%
See 1 more Smart Citation